'A good faithful pal': working relationships between humans and horses during the First World War. Issue 1 (2nd January 2021) - Wise, Nathan
ABSTRACT: There is growing scholarly interest in the history of human-animal relationships. With regards to the First World War, scholars have increasingly sought to understand the nature of those relationships throughout the international armed forces and to ascertain the contribution animals made towards various war efforts. This article focuses on relationships between service personnel and horses in the Australian Imperial Force during the First World War, and argues that relationships between soldiers and their horses varied, ranging from a strictly utilitarian approach that often resulted in the mistreatment of horses, through to a deeply caring approach that resulted in close bonds between humans and horses. As will be seen, the foundations for these differences were principally the nature of individual approaches to military service in general, and the specific nature of working relationships with horses. In addition to documenting these differences and emphasizing the importance of this working relationship, this focus on the AIF also demonstrates the need to consider and value the emotional and sentimental expressions of service personnel during the First World War.